Academic writing as sociolinguistic practice: The case of academic writing in foreign language studies - Evelyn Vovou (Peoples' Friendship University of Russia (RUDN University), 2023)
Academic writing often poses considerable difficulties that have to do with the way academic writing courses are conceived and the skills students are taught within this context. Especially students in foreign language studies deal with additional difficulties that are related to their self-perception as scholars, to their somewhat limited experience within the academic environment and to expressing logical/epistemic thinking in the foreign language. The aim of the study presented in this paper is to explore the nature of academic writing as a sociolinguistic practice. Research questions are: how do (a) the lack of sociolinguistic lived experience within academia, (b) the discrepancies between first and foreign language, (c) the absence of the core skills of grammar, logic and rhetoric influence academic writing? Participants in the study attended an academic writing workshop. Data was gathered using Contextual Inquiry by means of observation grids and semi-structured interviews. Results show that (a) even high-achieving students exhibit feelings of incompetence when it comes to academic writing, (b) the material of academic writing courses should include logical/epistemic thinking tasks, based on the training of core skills, (c) achievement in academic writing correlates with a sense of scholarship, (d) a distinction between social communicative and academic communicative language might be helpful. Academic writing courses should take existential, declarative as well as linguistic knowledge into consideration. The study concludes that it is advisable to integrate logical and epistemic thinking training into academic writing courses, broadening their scope. Alternatively, introducing a separate logical and epistemic thinking course would be more advantageous. This approach is preferable because logical and epistemic thinking extends beyond writing (such as papers and theses) to encompass spoken communication (presentations) and reading (strategies for literature search and synthesis).